An investigation of a realistic, field scale CO2-plume geothermal system a case study of the Mindanao Geothermal Production Field - Alcaraz, Joselito "Yam" T. II; Beranda, Menandro S.; Resurreccion, Augustus C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The use of CO2 as working fluid in an Enhanced Geothermal System (EGS) has been studied because of its thermodynamic and hydraulic advantages over water, and its ancillary benefit of sequestering carbon dioxide deep under the earth's surface. Research on the thermodynamics, chemistry, and economics of CO2-Plume Geothermal (CPG) based systems has proliferated, but most has been limited to homogeneous representations of reservoir models. Thus, in this study, a realistic, field-scale model is created to better assess the viability of a CPG system. Considering measured data from the MGPF (Mindanao Geothermal Production Field), the numerical simulator FEHM (Finite Element Heat and Mass Transfer) was used to calibrate a natural state model which was reasonably matched with the measured borehole temperature and pressure data. Placement of CO2 injection and production wells was investigated by simulating forecast scenarios of the CPG system. Parameter sensitivity studies were done due to the large uncertainty of reservoir permeability and porosity values. Optimization of production mass flow rates was done to maximize the overall heat extraction from the reservoir Wells located in the Marble area has significantly higher heat extraction rates than its Matingao counterpart. Thermal siphoning on the other hand is more plausible within the Matingao sector, i.e. Matingao sector wells have higher pressure differential between production and injection wellheads compared with Marbel wells.
Thesis (M.S. Mechanical Engineering)--University of the Philippines Diliman
Keywords: Geothermal resources